Statistical Evaluation of Fodder Trees Under an Agroforestry System - Jaggi, Seema; Gill, A. S.; Varghese, Cini; Sharma, V. K.; Singh, N. P. (Indian Forester, 2011)
Fodder trees in agro-forestry system are planted to overcome the effects of the seasonal shortages or to insure against risks of drought and also to deliver benefits such as shelter, soil conservation, timber and fuel wood. An attempt was made to investigate the performance of fodder trees in the presence and absence of crops. The data pertaining to growth parameters and biomass parameters of the four fodder trees from an agro-forestry experiment for six years (1999-2005) was analyzed. Contrast analysis has been performed to study the performance of the different tree species with and without crops. The combined analysis of the tree data over the years was also performed.